Applying a systems oriented ethical decision making framework to mitigating social and structural determinants of health - Smith, Carlos S. (Frontiers in Oral Health, 2023)
Objectives Clinical ethical decision-making models are largely geared toward individual clinician choices and individual patient outcomes, not necessarily accounting for larger systemic issues that affect optimal patient outcomes. The purpose of this paper is to provide an ethical decision-making model, drawing upon systems orientation and ethical theory, specifically incorporating and aiding in the mitigation of social and structural determinants of health. Methods This paper presents a systems-oriented ethical decision-making framework derived from the analysis and critique of the Four-Box Method for Ethical Decision-Making by Jonsen, Siegler, and Winslade. Drawing upon both deontological and utilitarian ethical theory, the developed framework will assist providers, organizations, and health system leaders in navigating the increasingly complex ethical dimensions of care delivery for underserved patient populations, who are largely impacted by social and structural determinants of health. Results The needs of underserved patients are inextricably linked to various social and structural determinants of health that, if left unaddressed, result in even poorer health outcomes, exacerbating existing health disparities. A systems-oriented ethical decision-making framework, centered on obligation, duty, and a utilitarian view of the optimal good, will aid providers, organizations, health system leaders, and community stakeholders in navigating the increasingly complex ethical dimensions of care delivery for underserved patient populations. Conclusion Socioeconomic and political contexts have a significant impact on the way society is organized, how people are positioned in society, and how they will fare in terms of their health. Healthcare providers, including dentists, are largely unaware of and insensitive to the social issues that underlie the biological or psychological concerns that patients from socially disadvantaged backgrounds face. A systems-oriented ethical decision-making model will aid in mitigating social and structural determinants of health and the dental profession's obligations to the underserved.